(untitled) - Sparks, Glenn Grayson (Belmont, CA, 2002)
his exciting new text provides an excellent introduction for students of mass media effects. Through an engaging, narrative style, the author presents the fascinating research findings of media impacts and the connected mass media theories in the context of those research findings. Students are provided with a clear perspective of the relationship between science, methods, and the practical questions of the effects of mass media
Keywords: Mass media,Mass media,Truyền thông đại chúng,Truyền thông đại chúng; Social aspects,Research,Methodology,khía cạnh xã hội,Phưong pháp,Nghiên cứu